Prevalence and correlates of depression, anxiety and trauma-like symptoms in Chinese psychiatric patients during the fifth wave of COVID-19 pandemic: a cross-sectional study in Hong Kong - Joe Kwun Nam Chan; Don Ho Hin Chang; Vivian Shi Cheng Fung; Eileena Mo Ching Chui; Corine Sau Man Wong; Ryan Sai Ting Chu; Yuen Kiu So; Jacob Man Tik Chan; Albert Kar Kin Chung; Krystal Chi Kei Lee; Calvin Pak Wing Cheng; Heidi Ka Ying Lo; et al. (BMC Psychiatry, 2024)
Abstract Background Psychiatric patients are susceptible to adverse mental health outcome during COVID-19 pandemic, but its associated factors are understudied. This observational cross-sectional study aimed to comprehensively examine prevalence and correlates of psychological distress, in terms of depression, anxiety and post-traumatic-stress-disorder (PTSD)-like symptoms, among Chinese adult psychiatric outpatients amidst the peak of fifth COVID-19 wave in Hong-Kong. Methods A total of 415 patients (comprising 246 patients with common-mental-disorders [CMD] and 169 with severe-mental-disorders [SMD]) and 399 demographically-matched controls without mental disorders were assessed with self-rated questionnaires between 28-March and 8-April-2022, encompassing illness profile, mental health symptoms, psychosocial measures (loneliness, resilience, coping styles) and COVID-19 related factors. Univariate and multivariable logistic regression analyses were conducted to determine variables associated with moderate-to-severe depressive, anxiety and PTSD-like symptoms among psychiatric patients. Results Our results showed that CMD patients had the greatest psychological distress relative to SMD patients and controls. Approximately 40–55% CMD patients and 25% SMD patients exhibited moderate-to-severe depression, anxiety and PTSD-like symptoms. Multivariable regression analyses revealed that female gender, lower educational attainment, single marital status, being housewife, more severe insomnia, psychotic-like symptoms and cognitive complaints, self-harm behavior, lower resilience, avoidance coping, never contracting COVID-19 infection, greater fear of contagion, and longer exposure to pandemic-related information were independently associated with depression, anxiety and/or PTSD-like symptoms in psychiatric patients. Conclusions Our results affirm increased vulnerability of psychiatric patients toward psychological distress during pandemic. An array of identified correlates facilitates early detection of high-risk psychiatric patients for targeted strategies to minimize pandemic-related negative psychological impact.